Floral Motifs in South Italian Vase Painting: Problems of Studying - Kifishina, Oxana A. (Actual Problems of Theory and History of Art, 2016)
This article focuses on the study problems of floral motifs in South Italian vase painting. Floral motif in the decor system of Late Greek red-figure vases still remains insufficiently explored. This study intends to indicate the range of major issues and problems related to plant images in red-figure vases of South Italia. Nowadays, it is common to study floral motifs in the framework of resolving the problem of an author’s handwriting. The research on the iconography of antique flowers — especially acacias, poppies and roses — and their semantic analysis can also be considered as promising. The semantic analysis is particularly effective in Orphic and heortological contexts (or a feast system by the example of Rosaliae). The author shows that these days all three sets of scientific problems remain relevant.
Keywords: South Italic vases; floral motifs; stylized flower; hybrid form; myth and ritual tradition; Orphism; Rosaliae